Mechanisms of False Alarm in Response to Fear Stimulus: An Event-Related Potential Study - Wang, Xiai; Sun, Jicheng; Yang, Jinghua; Cheng, Shan; Liu, Cui; Hu, Wendong; Ma, Jin (Frontiers in Human Neuroscience, 2022)
Background and Objective: There is a paucity of research that has explored "False Alarm" mechanisms. In order to remedy this deficiency in knowledge, the present study used event-related potential (ERP) technology to reveal the mechanisms underlying False Alarm in response to fear stimuli. Methods: This study selected snakes as experimental materials and the "oddball paradigm" was used to simulate the conditions of False Alarm. The mechanism underlying False Alarm were revealed by comparing cognitive processing similarities and differences between real snakes and toy snakes. Results: ERP findings demonstrated that there was no significant difference between N1 and P2 components induced by real and toy snakes in the early processing stage. Compared with toy snakes, real snakes induced a smaller N2 amplitude, larger P3 amplitude and a shorter P3 latency at the late processing stage. The results of brain topographic mapping analysis showed that the brain regions activated by a real or toy snake were basically the same within the time windows of 110-150 ms and 220-270 ms, respectively. In the time window of 300-360 ms and 400-500 ms, the degree of brain regions activation with a real snake was significantly greater than that induced by a toy snake. Conclusion: False Alarm is caused by the brain's inability to distinguish, in the early stage of cognitive processing, stimulus objects with similar appearances. When the brain is able to distinguish the differences between different stimulus objects in the late stage of cognitive processing, False Alarm disappears.